Strategi Promosi Berbasis Digital Marketing dalam Meningkatkan Minat Calon Peserta Didik Baru di Sekolah - Siti Fatikhatus Sya’adah (Lembaga Pengembangan Kinerja Dosen, 2024)
Educational institutions currently need to be managed competently and deserve attention in today's era. Because, school competition is getting tighter. to influence the decisions of parents and prospective students in accepting new students. Schools need to have the right promotional strategy. Because the more competitive schools are, the more schools must have good and innovative promotional strategies to attract consumer interest. In an era that relies on technology and the target market that currently understands technology, educational institutions are required to adapt to technological developments, one of which is through the implementation of digital marketing-based promotional strategies. Schools can promote through Digital Marketing by using the school website or utilizing social media sites such as Facebook, Instagram, Twitter, TikTok, YouTube, and Whatsapp. The purpose of this study is to examine how digital marketing-based promotional strategies can help schools increase the interest of prospective new students. This study uses a literature study method based on various sources in the form of reference books, research results, or scientific journals. Thus, the use of the right promotional strategy, especially in using school digital marketing, can reach a wider community, school information becomes easily accessible anytime and anywhere, and this school's promotional activities will certainly be more effective and efficient.